Improved stability and access time Using Different 6T SRAM Cells at Low Voltage - Raturi, Ashish; Bhatt, Kamlesh (International Journal of Computer Sciences and Engineering, 2019)
Contradictory nature of read and write stability and stability with speed necessitates the use of FinFET device which has less statistical variability, sensitivity and more on current. In this work, we explored three different FinFET device structures. These structures are used to form three different 6T SRAM cells. All the simulations are done with the help of Sentaurus TCAD. Three SRAM cells are compared to reduce access time and enhance data stability. We found that ADSE FinFET SRAM achieve significant improvement in access time as compared to Underlap FinFET SRAM cell without degradation of cell stability. On the other hand High-k spacer SRAM cell shows noteworthy increase in stability over other two cells with somewhat slower response.